Peran KUA dalam Menanggulangi Perkawinan Tidak Tercatat (Nikah Siri) di Kecamatan Kota Tengah Kota Gorontalo - Mohamad Irvan Fahrizal Ginintu; Nur Mohamad Kasim; Julius T. Madjo (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The aim of this research is to address the role of the KUA in overcoming unregistered marriages (Nikah Siri) in Kota Tengah District, Gotontalo City and the factors that hinder the role of the KUA itself in unregistered marriages (Nikah Siri). This type of research is Normative Empirical research using a qualitative descriptive approach, analyzing information and interpreting qualitative data. The research results show that the role and efforts of the KUA have not been effective in dealing with unregistered marriages (Nikah Siri) even though they have implemented a government program, namely the marriage guidance program (Binwin), which provides pre-marital guidance and the formation of sakinah families in order to build superior human resources and reduce the divorce rate. by providing counseling about marriage registration and sakinah families to prospective couples who are about to get married and also by conducting outreach to the wider community. The factors that hinder the KUA in preventing unregistered marriages for couples who are not legally married in Kota Tengah District are caused by 2 factors, namely, internal factors, namely the lack of competent human resources who can provide socialization to the community, and the lack of adequate facilities and other factors. Other external factors include indifferent attitudes, non-compliance with the law, and low legal awareness in society. Therefore, we must work together with agencies such as the KUA in building character and also informing millennials about the impacts of having a relationship before marriage so that there is no such thing as an unregistered marriage.